Study of Educational Theory from Ibn Khaldun's Perspective - Hoirul Anam; Ahmad Arifi; Nasiruddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Ibnu Khaldun is a figure who has made many contributions to the world of education. However, as time went by, the ideas he put forward were widely ignored by today's scientific circles, even though in fact many western educational figures quoted his paradigm. Like Adam Smith, Max Weber, and Arnold Y Toynbee and others. The aim of the research carried out by this author was nothing more than to find out about Ibn Khaldun's paradigm which could be used as a theory. The research method used by the author uses literature/research library research. The data used in this research is divided into two parts. First, primary data, which consists of the Muqaddimah of Ibn Khaldun. Second, secondary data, consisting of books, books, journals, which are related to the research studied by the author. The results of this research show that Ibn Khaldun's paradigm which can be used as a theory has four points. Firstly, Malakah is a characteristic that is ingrained and rooted, which can be produced by repeated learning. Second, generalization, namely the learning that is carried out, is recommended for students to be taught things that are general and simple, especially things related to things that are the basis for the discussion they are studying. The third tadaurrj is that learning is considered effective. If learning is done gradually. Fourth, continuity, namely learning that is interrupted over a long period of time in entering one material into another, can cause the knowledge that is being studied to be incomplete and easy to forget.